2015
DOI: 10.1111/bjh.13641
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation activation in sickle cell trait: an exploratory study

Abstract: Summary Recent epidemiologic data suggest that sickle cell trait (HbAS; AS) is a risk factor for venous thromboembolism. We conducted an exploratory study of healthy subjects with AS under baseline conditions to determine whether a chronic basal hyperactivation of coagulation exists, and if so, what mechanism(s) contribute to this state. Eighteen healthy AS individuals were compared to 22 African-American controls with a normal haemoglobin profile (HbAA; AA) and 17 patients with sickle cell disease (HbSS; SS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 55 publications
0
21
1
Order By: Relevance
“…5 While sickle cell disease is a hypercoagulable state, few prior studies have examined hemostatic measures in HBB rs334 heterozygotes. 5, 30, 31, 33 We did not find any association between HBB rs334 and other hemostasis biomarkers, though our analysis may be limited by sample size. The mechanism responsible for higher D-dimer in sickle cell mutation carriers is unknown.…”
Section: Discussioncontrasting
confidence: 57%
“…5 While sickle cell disease is a hypercoagulable state, few prior studies have examined hemostatic measures in HBB rs334 heterozygotes. 5, 30, 31, 33 We did not find any association between HBB rs334 and other hemostasis biomarkers, though our analysis may be limited by sample size. The mechanism responsible for higher D-dimer in sickle cell mutation carriers is unknown.…”
Section: Discussioncontrasting
confidence: 57%
“…Thrombin generation assays (TGA) reliably assess an individual’s rate and potential to generate thrombin ex vivo in plasma and possibly in whole blood, following a calibrated trigger of coagulation (27,28). Although multiple studies are published (2932), the results of ex vivo TGA in SCD patients at “steady state” compared with age-matched controls or with patients during acute painful episodes are inconsistent. This inconsistency may be due to heterogeneity in the genotypes and treatments of enrolled subjects, lack of race-matched controls in some studies, variability in the timing of blood collection, sample preparation and/or the analytical conditions of the assays (Table 1).…”
Section: Hemostatic Alterations Of Scdmentioning
confidence: 99%
“…Two small case-control studies have shown an association of SCT to D-dimer, but these analyses were limited by sample size and lack of adjustment for confounders. 15,16 A recent, larger prospective study by Folsom et al evaluating the relationship of D-dimer with future VTE noted higher D-dimer levels among SCT carriers, but this association was not further quantified. 21 That study also found that D-dimer elevations conferred a stepwise increase in risk of future VTE, but that the presence of SCT did not fully modify or explain the association of D-dimer with VTE.…”
mentioning
confidence: 99%